An Unpublished Tremissis in the Name of Honorius - Faltin, Dirk (KOINON: The International Journal of Classical Numismatic Studies, 2022)
This article presents an unpublished tremissis in the name of Roman Emperor Honorius (AD 393–423) (cf. Figure. 1). The coin was sold by a Spanish auction house and is in the possession of the author. The auction catalogue described the coin as a possible barbarous imitation (‘Acunacion Barbara?’). This article proposes an attribution of the coin to the 5th-century kingdom of the Suevi on the Iberian Peninsula. If correct, the coin fills an important gap in the Suevic coin series.